2022
DOI: 10.4102/sajems.v25i1.4358
|View full text |Cite
|
Sign up to set email alerts
|

The significance of an employee value proposition in the retention of teachers at selected South African private schools

Abstract: For any school management team, the challenge is to find and retain quality teachers -teachers with the skills, knowledge, experience, competencies and values that provide a match for the roles within the organisation. Teachers look around, think about their circumstances, compare options, and then choose to take up or stay in positions based on the best value offered to them, as characterised by the EVP. An attractive EVP will also ensure the commitment and engagement of employees, the result of which would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…Although Adekoya, Ajonbadi, Okorie and Jimoh (2021) found that there is still need for the reinforcement of HRM regarding the facilitation of work-life balance policies for talent attraction and retention purposes in UAE education sector. This is similar to the findings of Swanepoel and Saurombe (2022) that in the South African context, there deficiencies employee value proposition (EVP), basically an exchange of perceptions of loyalty between employer and employees. The perceptions of loyalty are a two-way process, employees are loyal to retaining their roles as long as they have the perceptions that their employers are equally loyal to the relationship (Yesufu, 2020).…”
Section: Training and Development: It Comprises The Formalsupporting
confidence: 88%
“…Although Adekoya, Ajonbadi, Okorie and Jimoh (2021) found that there is still need for the reinforcement of HRM regarding the facilitation of work-life balance policies for talent attraction and retention purposes in UAE education sector. This is similar to the findings of Swanepoel and Saurombe (2022) that in the South African context, there deficiencies employee value proposition (EVP), basically an exchange of perceptions of loyalty between employer and employees. The perceptions of loyalty are a two-way process, employees are loyal to retaining their roles as long as they have the perceptions that their employers are equally loyal to the relationship (Yesufu, 2020).…”
Section: Training and Development: It Comprises The Formalsupporting
confidence: 88%
“… Tomprou et al (2015) note that, unlike a formal contract, a psychological contract represents the intangible mutual beliefs, perceptions and informal obligations between an employer and an employee. Psychological contracts are informally established as an implicit agreement between the employee and the employer on the roles and activities that each party is going to perform without specifically elaborating on the details ( Swanepoel and Saurombe, 2022 ). It is predominantly subjective and dependent on what the employee and the employer believe is acceptable or not ( Rousseau et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The changes in the banking environment have brought a shift in the nature of the employer-employee relationship. Traditionally, the psychological contract has been geared to aspects such as trust, respect and loyalty between the employer and the employee ( Swanepoel and Saurombe, 2022 ). These relational aspects are still important, however, the recent insecure and changing work environment has brought a shift so that we are starting to see transactional exchange becoming more prevalent ( Braganza et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations